A 1.5-V 75-dB dynamic range third-order Gm-C filter integrated in a 0.18-μm standard digital CMOS process. - Yodprasit, U. (IEEE Journal of solid state circuits)
A design methodology of a CMOS linear transconductor for low-voltage and low-power filters is proposed in this paper. It is applied to the analog baseband filter used in a transceiver designed for wireless sensor networks. The transconductor linearization scheme is based on regulating the drain voltage of triode-biased input transistors through an active-cascode loop. A third-order Butterworth low-pass filter implemented with this transconductor is integrated in a 0.18-μm standard digital CMOS process. The filter can operate down to 1.2-V supply voltage with a cutoff frequency ranging from 15 to 85 kHz. The 1% total harmonic distortion dynamic range measured at 1.5 V for 20-kHz input signal and 50-kHz cutoff frequency is 75 dB, while dissipating 240 μW.